Reduction in Toxicity of Tectoquinone against Reticulitermes speratus Kolbe termites - Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2020)
The cause of low toxicity against Reticulitermes speratusKolbe termite species of teakwood under natural condition was investigated. Anti-termite test was conducted to evaluate the effectivity of four major components (tectoquinone, deoxylapachol, tecomaquinone, and squalene) of ethanol-benzene extracts in the teak heartwood. Tectoquinone exhibited both strong toxicity and antifeedancy as well as it was far superior to other components. The strength reduction of tectoquinone bioactivity is assumed due to interaction with other major components. As squalene was found in considerable amounts or 1.8 to 13.1 times as high as the tectoquinone concentration in woods, termite feeding was set to the mixtures of tectoquinone and squalene in various ratios (1:1, 1:5, 1:10, and 1:20). It was revealed that squalene addition could decrease the termite mortality 15% to 44% from its initial value (tectoquinone only). On the other hand, the mixtures reduced mass loss due to termite attacks only to a small degree.